Nutritional effects of transjugular intrahepatic portosystemic shunt - An often neglected benefit? - Rose, James E.; Gurakar, Ahmet O.; Duld, Sajid; Camci, Cemalettin; Parmalee, Trish; Nour, Bakr; Rizvi, Syed (Lippincott Williams & Wilkins, 2006)
[Abstract Not Available]
71st Annual Scientific Meeting of the American-College-of-Gasroenterology -- OCT 20-25, 2006 -- Las Vegas, NV